JUAL BELI TELUR BURUNG MURAI BATU DI DESA KARANGSARI KEC. KUTOWINANGUN KAB. KEBUMEN PERSPEKTIF HUKUM ISLAM - Muhamad Mustahal; Imadatul Khasanah (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2022)
Buying and selling, namely owning something property (money) by replacing something on the basis of a syara‟, or just having the benefits that the syara‟ allows by replacing (paying) a price similar to property (money). The practice of buying and selling Murai Batu bird eggs in Karangsari village, Kutowinangun sub-district, Kebumen district, payments are made using down payments. The sale and purchase transaction of bird eggs, the seller and the buyer, conducts a sale and purchase agreement for Murai Batu bird eggs at the beginning using the down payment system.  After the eggs are purchased, the broodstock incubates them until they hatch and only then is the payment paid and the chicks can be taken. The ijārah contract is identical to the sale and purchase contract, however, the ijārah contract for ownership of goods is limited by time. Etymologically, ijārah is the name for wages (ujrah). Meanwhile, the term ijārah is a contract or service or benefit that has economic value (maqshūdah), it is known, legally handed over to someone else, using a known wage. Then what is the review of Islamic law on the practice of buying bird eggs that occurred in Karangsari Village, Kutowinangun District, Kebumen Regency. The type of research used is field research. Using an analytic descriptive approach. In practice, buying and selling is justified because it is not against the law. However, the practice of ijᾱrah in these transactions is an unclear get along in ujrah. Included in the category of ijᾱrah dzimmah, but does not meet the payment requirements that must be paid in cash at the beginning of the agreement. Therefore, it can be concluded that the sale and purchase of Murai Batu bird eggs that occur in Karangsari Village, Kutowinangun District, Kebumen Regency is incorrect according to Islamic law.